Effect of spray-drying and storage conditions on the physical and functional properties of standard and n−3 enriched egg yolk powders. (June 2015) - Rannou, C.; Queveau, D.; Beaumal, V.; David-Briand, E.; Le Borgne, C.; Meynier, A.; Anton, M.; Prost, C.; Schuck, P.; Loisel, C.
Highlights: Physical properties of egg-yolk rehydrated powders are investigated. Enrichment with n−3 fatty acids contributes to innovative egg-yolk powders. Thermal properties, color and viscosity are linked to n−3 fatty acids enrichment. Abstract: This study aimed to evaluate the effect of the processing and storage conditions on the physical and functional properties of egg yolk (EY) powders. The spray-drying temperature (160 °C vs . 180 °C), storage temperature (15 °C vs. 30 °C) and time (1, 2, 4 and 8 months) and n−3 enrichment through hen diet were investigated. The spray drying temperature and storage conditions modified the water content, water activity and the particle size distribution of EY powders. Flowability of the powders and the emulsifying properties were not significantly affected from an industrial point of view. On the opposite, the viscosity increased with the spray-drying temperature as well as the temperature and time of storage in rehydrated powders. Powders prepared with n−3 enriched egg yolks exhibited lower melting peaks temperatures, a marked yellow colour and higher fluidity of the solutions, but the overall properties remained unchanged. This study clearly attests the possibility of an industrial production of n−3 enriched EY powders.